An in situ approach to the conservation of temperate cereal crop wild relatives in the Mediterranean Basin and Asian centre of diversity. Issue 2 (9th January 2019) - Phillips, Jade; Whitehouse, Katherine; Maxted, Nigel
Abstract: Cereal crops are one of the most widely consumed and most valuable crops for humankind. The species have been domesticated for over 10, 000 years and as such have lost much of the genetic diversity that is present within their wild relatives. Future breeding efforts will require the use of genetic diversity from crop wild relatives (CWRs) to help improve our cereal crops. This study aims to identify an in situ conservation network within the Mediterranean Basin and west Asia for the four cereal crops, barley ( Hordeum L.), oat ( Avena L.), rye ( Secale L.) and wheat ( Aegilops L., Amblyopyrum L., Triticum L.). This region is a centre of diversity for these taxa and an area of potentially high genetic diversity, which if left unprotected will not be available for plant breeders to utilize in the future. Presence point data for a total of 90 taxa were collected from GBIF and resulted in 76, 343 individual presence points across the 44 countries in the study region. Geographic Information System (GIS) software was used to identify potential in situ reserve networks per crop genepool and for all crops combined. Results indicate a network of 10 locations across the region which would protect over 80% of the taxa. The number one priority reserve is found within the Fertile Crescent region on the border of Israel, Syria and Jordan. This proposed reserve location contains 93 currently protected areas (i.e. National Parks) and as such, it may only be necessary to alter management plans to effectively protect CWR populations. For taxa not found within protected areas ex situ conservation may be more appropriate and should be implemented as a backup to the in situ reserve network.